Childhood‐onset systemic lupus erythematosus with trisomy X and the increased risk for bone complications: a case report - Susumu Yamazaki; Yuko Akutsu; Asami Shimbo; Masaki Shimizu; Yuko Segawa; Masaaki Mori (BMC, 2021)
Abstract Background Systemic lupus erythematosus is a multi-organ inflammatory autoimmune disease; immune complexes are part of the pathogenesis, but not entirely responsible. Trisomy X is the most common female chromosomal abnormality and the role of an additional X chromosome in the development of systemic lupus erythematosus is well recognized. However, the potential complications and optimal management of childhood lupus with trisomy X remain unclear. Herein, we describe a case of childhood-onset systemic lupus erythematosus associated with severe bone complications presumably secondary to trisomy X. Case presentation A 16-year-old Japanese girl was diagnosed with childhood-onset systemic lupus erythematosus and trisomy X. A chromosomal abnormality (47, XXX) was incidentally identified on bone marrow examination initially done to determine the cause of pancytopenia. She had a persistent headache, fever　for six days, diffuse hair loss, mucosal ulcers, butterfly eruptions, and palmar erythema. Furthermore, thrombocytopenia, anemia, and erythrocyte fragmentation were detected, suggesting secondary thrombotic microangiopathy. She was initially treated with intravenous methylprednisolone pulse therapy and prescribed monthly cyclophosphamide for severe disease activity, prednisolone, mycophenolate mofetil, and hydroxychloroquine as remission maintenance drugs. She developed generalized extremity pain that had been worsening throughout the disease. Extremity magnetic resonance imaging performed 12 months after the treatment onset revealed multifocal avascular necrosis, and dual-energy X-ray absorptiometry revealed further decreased bone mineral density. High plasma levels of factor VIII were detected by additional tests for coagulation functions, and we suspected the possibility that factor VIII might cause avascular necrosis due to thrombosis. Currently, she is being treated with prednisolone and MMF for SLE. However, her extremity pain has not been managed effectively even under the administration of non-steroidal anti-inflammatory drugs and pregabalin. Conclusions An additional X chromosome has been reported to be associated with factor VIII and osteoporosis. Additionally, elevated plasma levels of FVIII is the risk factors for thrombosis, which leads to the risk of avascular necrosis. Patients with systemic lupus erythematosus complicated by trisomy X might be at a higher risk of avascular necrosis and osteoporosis that can also manifest in childhood systemic lupus erythematosus.